2021
DOI: 10.4111/icu.20200319
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of urosepsis in struvite stone patients after percutaneous nephrolithotomy

Abstract: Purpose This study aims to identify clinical factors that may predispose struvite stone patients to urosepsis following percutaneous nephrolithotomy (PCNL). Materials and Methods A retrospective review was conducted on patients who received PCNL for struvite stones. The Systemic Inflammatory Response Syndrome (SIRS) criteria and quick-Sepsis Related Organ Failure Assessment (q-SOFA) criteria were used to identify patients who were at an increased risk for urosepsis. Sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 30 publications
1
6
1
1
Order By: Relevance
“…Consistent with the study of Chan et al 37 , duration of hospitalization was also identified as an independent risk factor for urosepsis among our patients' population. Prolonged hospitalizations are associated with a risk of infection, especially in those with multiple comorbidities 38 .…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with the study of Chan et al 37 , duration of hospitalization was also identified as an independent risk factor for urosepsis among our patients' population. Prolonged hospitalizations are associated with a risk of infection, especially in those with multiple comorbidities 38 .…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, through the early identification of the factors associated with urosepsis, it is significant to avoid serious postoperative complications. In our study, the incidence rate of postoperative urosepsis was 19.4%, which was higher than that reported in a previous study [ 5 ]. This may be related to all patients with diabetes enrolled in this study.…”
Section: Discussioncontrasting
confidence: 80%
“…Many studies have demonstrated the risk factors for urosepsis after PCNL [ 4 , 5 ], including staghorn calculi, positive midstream urine culture, preoperative stenting, and bladder outlet obstruction. However, at present, most studies ignore an important factor, namely intraoperative blood pressure, combined with intraoperative anesthetic blood pressure.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study identified some predictors of urosepsis after PCNL treatment for struvite stones: higher preoperative white blood cell count, greater total stone surface area, preoperative stenting, recent use of antibiotics, and obstructive uropathy [ 43 ]. In another study, sepsis was approximately four times more common in patients with struvite stones treated with PCNL.…”
Section: Resultsmentioning
confidence: 99%